INTERACTIVE MULTIMEDIA DEVELOPMENT USING GOOGLE SITES TO IMPROVE STUDENT LEARNING OUTCOMES AND ENERGY - Ayu Wulandari; Lukman Hakim; Rita Sulistyowati; Yusuf Mian (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2022)
The use of interactive multimedia is very important to develop in physics learning. The purpose of this study is to develop interactive multimedia base google sites on the subject of work and energy to improve the learning outcomes of class X students of SMA Bina Warga 1 Palembang which are valid, practical and have a potential effect. The method used is Research and Development with a rowntree development model consisting of several stages, namely: planning, development and evaluation. The evaluation used is a modified Tassmer evaluation consisting of self-evaluation, expert review, one to one, small group, and field test. The data collection technique uses a walkthrough to test the validity of the product which consists of three validators to assess the product from the material, media and language aspects, one to one and small group stages to test the practicality of the product developed. The results showed that interactive multimedia was valid and practical (3.56 interformations were very valid) and (94% were very practical stage one to one, 87% were very practical small group stage) for the N-Gain value obtained an average of 0.72 high category. So it can be concluded that interactive multimedia in the form of google sites is suitable for use in learning physics.AbstrakPenggunaan multimedia interaktif sangat penting untuk dalam pembelajaran fisika. Tujuan penelitian ini adalah mengembangkan multimedia interaktif berbasis google sites pada pokok bahasan usaha dan energi untuk meningkatkan hasil belajar siswa kelas X SMA Bina Warga 1 Palembang yang valid, praktis dan memiliki pengaruh potensial. Metode yang digunakan adalah Research and Development dengan model pengembangan rowntree yang terdiri dari beberapa tahapan yaitu: perencanaan, pengembangan dan evaluasi. Evaluasi yang digunakan adalah modifikasi evaluasi Tassmer yang terdiri dari evaluasi diri, expert review, one to one, small group, dan field test. Teknik pengumpulan data menggunakan walkthrough untuk menguji validitas produk yang terdiri dari tiga validator untuk menilai produk dari aspek materi, media dan bahasa, tahap one to one dan small group untuk menguji kepraktisan produk yang dikembangkan. Hasil penelitian menunjukkan bahwa multimedia interaktif valid dan praktis (3,56 interformasi sangat valid) dan (94% sangat praktis tahap 1-1, 87% sangat praktis tahap kelompok kecil) untuk nilai N-Gain diperoleh rata-rata 0,72 tinggi kategori. Sehingga dapat disimpulkan bahwa multimedia interaktif berupa google sites cocok digunakan dalam pembelajaran fisika.How To Cite: Wulandari, M., Hakim, L., Sulistyowati, R., Mian, Y. (2022). Interactive Multimedia Development Using Google Sites to Improve Student Learning Outcomes and Energy. EDUSAINS, 14 (2) : 188-201.